How Credit-Money Shapes the Economy : The United States in a global system - Guttmann, Robert (Armonk, N.Y. : M.E. Sharpe, 1994)
This text examines money, credit, and economic activity in the increasingly integrated global economy. It focuses on the problems afflicting the United States as it adapts to the transformation of the world economy.
Includes index.
Includes bibliographical references (p. 527-539).
rpm 08/09/16
Loans
Keywords: Monetary policy; Money -- Social aspects -- United States; Money; Gold standard; Credit; Banks and banking; International finance